THE CONVERGENCE OF PHYSICAL EDUCATION TO ENERGY BALANCE PRACTICES (Fiep Bulletin - online, 2019)
This article discusses the convergence of physical education to energy balance practices; in relation to theelectromagnetic field of the body. Likewise, it suggests the unpredictable movement of Physical Education favorable to the basicprinciples advocated over time; being, awareness and health principle, references in the alleged article. Consequently, it aims topresent the Physical Education Professional as a parameter to energy balance practices. Also, practices that aim to balance theindividual as being conscious and integrated to the expanded view of the concept of health. Therefore, mention Meditation and Reikias techniques of energy balance pertinent to the set of promising practices to Physical Education, because they are plausible forintegral health. However, the article mentions the need for physical exercise in accordance with energy balance practices. Equitably, itleads to the perception of the body's physical and electromagnetic field by energetic correspondence, therefore, pertinent to wellbeingand integral health. Therefore, the above does not limit who conducts the practices, but it guides how much it is necessary toconverge to the Physical Education to the practices of energetic balance.